Le numérique à l'université : facteur explicatif des méthodes pédagogiques ? - Amélie Duguet; Sophie Morlaix
This article has a double ambition. Its primary purpose is to focus on the pedagogical methods deployed at the university by teachers in lectures and in practical work and tutorials. He is also interested in the use of digital technology by teachers, during and outside class time, as an explanatory factor for the pedagogical methods put in place. Thus, from the data collected through an empirical survey of a sample made up of 248 teachers from a French university, we propose a description of the pedagogical methods used by them. We then constructed regression models to explain teachers 'teaching methods, incorporating variables related to teachers' personal characteristics, the teaching context and their representation, their training and their use of ICT. We highlight a positive and significant effect of the use of certain digital technologies on the deployment of pedagogies designed to make students more involved in their learning. This work offers many lines of research concerning the link between the use of ICT and the teaching methods of university teachers. It also opens the debate on how these could be trained to take into account the heterogeneity of the student public in their digital pedagogical practices.